Indonesian Diplomacy in the Russia - Ukraine Conflict: A Study on Soft-Power: Diplomasi Indonesia dalam Konflik Rusia - Ukraina: Sebuah Kajian Tentang Soft-Power (Journal of Political Issues, 2023)
The Russia-Ukraine conflict has a negative impact on global stability, thus triggering crises in various countries. Conflict conditions that have not subsided, making Indonesia take the initiative to carry out a peace mission through President Joko Widodo who visited Ukraine and Russia, to become a communication bridge between the two countries. This study aims to explain the reasons why Indonesia carried out a peace mission against the Russia-Ukraine conflict. The research used a qualitative explanatory method, with library research data collection techniques, as well as qualitative analysis techniques. Besides that, it also uses Soft Power Theory, and the Concept of First Track Diplomacy. The results obtained were that Indonesia used first-track diplomacy instruments in the Russian-Ukrainian conflict peace mission, which can be seen from the use of dialogue, negotiation and cooperation between countries, thereby opening up opportunities for peace between countries. In addition, behind the peace mission, Indonesia has economic interests, forms a positive image, and prepares to launch the agenda for the upcoming G20 summit. This phenomenon is in line with the goal of Soft Power Indonesia, which is to improve the security of the external environment by projecting a peaceful and attractive image of the country by using its Soft Resources as Host & Chair of the G20 Summit. This study builds on previous studies, because the results obtained enrich the study of the development of the Russia-Ukarina conflict, especially when viewed from the perspective of soft power.
Keywords: Diplomacy; Soft Power; World Peace